On the verge of diagnosis: Detection, reporting, and investigation of de novo variants in novel genes identified by clinical sequencing. Issue 11 (11th October 2018) - Thiffault, Isabelle; Cadieux‐Dion, Maxime; Farrow, Emily; Caylor, Raymond; Miller, Neil; Soden, Sarah; Saunders, Carol
Abstract: The variable evidence supporting gene–disease associations contributes to the difficulty of accurate variant reporting in a clinical setting. An evidence‐based scoring system for evaluating the clinical validity of gene–disease associations, proposed by ClinGen, considers experimental as well as genetic evidence. De novo variants are heavily weighted, given the overall rarity in the genome and their contribution to human disease, however they are reported as "genes of unknown significance" in our center when there is insufficient evidence for the gene–disease assertion. We report a collection of 21 de novo variants in genes of unknown clinical significance ascertained via clinical testing, of which eight of 21 (38%) are predicted to cause loss of function. These genes were subjected to ClinGen scoring to assess the strength of gene–disease relationships. Using a cutoff for moderate high or strong, 10 of 21 genes now have sufficient evidence to qualify as likely pathogenic or pathogenic variants. Sharing such cases with phenotypic data is imperative to strengthen available genetic evidence to ultimately upgrade clinical validity classifications and facilitate accurate molecular diagnosis. Abstract : In this study, we investigate the detection, reporting and re‐interpretation of de novo variants in novel genes uncovered by clinical next‐generation sequencing. These novel genes were subjected to ClinGen scoring to assess the strength of gene‐disease relationships and facilitate accurate molecular diagnosis.